Oral Hygiene Practices: Ancient Historical Review - Gurudath, G; Vijayakumar, KV; Arun, R (Journal of Orofacial Research, 2012)
The ancient history of the world’s fascination with oral health is a long and illustrious one. Numerous dental epidemiological studies indicate that people are keeping their teeth longer than over before in this century. Neolithic age and prehistoric age people used agents and devices that have evolved, by custom, myth, beliefs and by research, to enable people, withprofessional assistance, to maintain good oral health. The first mentions of teeth and dental hygiene were found in inscriptions from Mesopotamian clay tablets, so called ‘oral hygieneproducts’ including toothpicks, chewing sticks, tooth powders and mouthwashes, dating back to 5,000 years ago. The Egyptians, Mesopotamians’, Greco-Romans, Hindus and Chinese discovered variety of dental treatments and intricate surgical operations. The profession has met the challenge by developing and perfecting a myriad of devices and agents tothwart these pathogenic factors since ages. We certainly eat well, speak well, look fine and ‘smell fresh’–but we also have plaque, gingivitis and dental caries. The reader can determinehow much our ancestors thought, invented and practiced oral hygiene long long ago and which gave raise to later inventions.